PENGARUH TEKNOLOGI INFORMASI, BUDAYA ORGANISASI, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN - Mohammad Imanda Prastyawan Yudha Pratama (2022)
The purpose of this study was to determine the effect of information technology, organizational culture, and environmental uncertainty on the quality of management accounting information systems. The sample used in this study were employees of the BRI Bank Company. The Quota Sampling technique was used in this study. Structural Equation Modeling (SEM) using Smart Partial Least Square version 3.0 is the method used to analyze the data. The results of this study indicate that information technology and organizational culture have a significant influence on the quality of management accounting information systems. Meanwhile, environmental uncertainty does not affect the quality of management accounting information systems.